A commentary on selected speeches of Isaios - Griffith-Williams, Brenda. (Mnemosyne, Supplements, 2013)
In A Commentary on Selected Speeches of Isaios , Brenda Griffith-Williams offers a fresh insight, accessible to non-Greek readers, into four disputed inheritance cases from the Athenian courts in the 4th century B.C. The only comprehensive English language commentary on Isaios (Wyse, 1904) reflects a negative view of the Athenian legal system as one in which the judges, who had no legal training, could be easily outwitted by an unscrupulous speechwriter with no regard for the truth. By addressing the complex interplay of factual, legal, and rhetorical issues in the selected speeches, Brenda Griffith-Williams identifies the strengths and weaknesses of each speaker's case and presents a more balanced assessment of Isaios's work.